Istnieć w czasie według Romana Ingardena - Zięba, Włodzimierz (Humaniora. Czasopismo Internetowe, 2025)
In the text, I analyze the existence of temporal objects, i.e. an event, process and object lasting in time, from the perspective of Roman Ingarden’s existential ontology. I show their existential specificity. An event exists only in a certain present. The process continues in time but as a continuity of individual phases, constituting its objective side, i.e. the subject of process ownership. An object that lasts in time, on the other hand, is fully present at every moment of its existence. I also show the relationships between events, processes and objects over time. I conclude that a pluralistic ontology containing events, processes and objects lasting in time provides the most complete description of the world.